The Pediatric Surgical Approach to Treating a Newborn with Suspected Intestinal Obstruction (International Journal of Food and Nutritional Sciences, 2022)
This article reviews the potential hazards to watch out for while examining a newborn with intestinal blockage and suggests a diagnostic algorithm. The discovery of a child who is otherwise healthy in the majority of surgical problems and the fact that many symptoms are modest are among the challenges. Correct radiographic interpretation is essential for making the diagnosis of distal intestinal blockage. The neonatologist and pediatric surgeon face a diagnostic difficulty when a newborn presents with symptoms of intestinal blockage. Nevertheless, a correct and prompt diagnosis will be possible in some cases with the help of a methodical interpretation of the history, physical examination, radiograph, and contrast imaging.